Acid tolerant multicomponent bacterial enzymes production enhancement under the influence of corn cob waste substrate - Srivastava N.; Singh R.; Mohammad A.; Pal D.B.; Ahmad I.; Alam M.M.; Mishra P.K.; Gupta V.K. (My University, 2025)
Cellulase enzymes have wide range of industrial application, but high production cost and relatively low efficiency are the main issues, which are needed to resolve. Substrate is known as the main contributor which can bring down the production cost of these enzymes at large scale. Therefore, in the present study, corn cob (Cc) waste has been employed as a potential substrate to produce efficient and good amount of cellulase using the bacterial strain Bacillus subtilis. Under the influence of optimal parameters while using the optimum concentration of Cc (7.0 g), maximum 12 IU/gds FP, 97 IU/gds BGL and 129 IU/gds EG have been recorded. Additionally, crude enzyme showed maximum FP activity of 14 IU/gds using 1.0 g/L peptone employed as the optimum organic nitrogen source. The bacterial cellulase exhibits temperature tolerance ability at 55 °C, and retains its half-life activity for 5 h and pH tolerance at pH 7.0 up to 55% of the relative activity. The results recorded in the present study may have potential for the large-scale and low-cost bacterial cellulase production using cellulose rich substrate e.g. Cc waste that can be vital for numerous industrial applications. © 2022 Elsevier B.V.